PENGARUH MANAJEMEN KELAS BERBASIS PEMBELAJARAN MENDALAM (DEEP LEARNING) DAN TEKNOLOGI DIGITAL TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 3 ADIANKOTING - Irene; Elisamark Sitopu; Wolter Parlindungan Silalahi (STKIP Subang, 2026)
The objectives of this study were: 1) To determine and examine whether there is an influence of deep learning-based classroom management on students’ learning motivation at SMP Negeri 3 Adiankoting; 2) To determine and examine whether there is an influence of digital technology-based classroom management on students’ learning motivation at SMP Negeri 3 Adiankoting; and 3) To determine and examine whether there is a simultaneous influence of deep learning-based classroom management and digital technology on students’ learning motivation at SMP Negeri 3 Adiankoting. This study employed a quantitative research method. The population of this study consisted of all students of SMP Negeri 3 Adiankoting during the academic year in which the research was conducted, totaling 182 students. The sample consisted of 125 students selected using the Slovin formula with a 5% margin of error. Data were collected through a closed-ended questionnaire consisting of 125 items. The results of the data analysis indicated that: 1) The value of t-count was greater than t-table for the influence of deep learning-based classroom management on students’ learning motivation (8.621 > 1.9799), indicating a positive and significant influence of deep learning-based classroom management on students’ learning motivation at SMP Negeri 3 Adiankoting, with a contribution of 37.7%; 2) The value of t-count was greater than t-table for the influence of digital technology on students’ learning motivation (6.514 > 1.9799), indicating a positive and significant influence of digital technology on students’ learning motivation at SMP Negeri 3 Adiankoting, with a contribution of 25.6%; and 3) The value of F-count was greater than F-table for the simultaneous influence of deep learning-based classroom management and digital technology on students’ learning motivation (45.527 > 3.07), indicating a positive and significant simultaneous influence of deep learning-based classroom management and digital technology on students’ learning motivation at SMP Negeri 3 Adiankoting, with a contribution of 42.7%. Therefore, Ha was accepted and H0 was rejected